(3JMaI GdQhGO aj PcQ edhc Hfi YHO GdhGOs - (3CHh RcQjG jMji Hf NdOhfs
(3ChdgG (B:s
(3fUdi Ydi SjOfG hehdGfG eMeO eUWafG GdeNJGQ hdeG cGf ehdGfG GdSdWGf QCjJ Cf EeJKGd CeQg GdYRjR Ydi aQUI aEfJOHJ dEedGA gPG GdcJGH s
(3BNQgG (B:s
(3QaYG SeGA Gdedc ahb HSjWI cHQi GdSjGSI GdCcfGa (B( (3ai PcQ MhGOK SfI (B776 (3g` (B) s
(3hgj Ydi KdGKI CbSGes
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(1655) s
Keywords: (3GdJGQjNs